Design, construction, and validation for in-situ water layer thickness determination during accelerated corrosion testing. (October 2020) - Katona, R.M.; Tokuda, S.; Perry, J.; Kelly, R.G.
Graphical abstract: Highlights: Creation of sensor for water layer determination, ranging from 0−5 mm, in salt spray testing environments. Water layers measured in continuous salt spray test similar to ASTM B117. Angle of exposure in standards determines if thin film regime is achieved influencing corrosion rate. Severe angles of exposure (>20 degrees) causes quasi-periodic run-off of water moving from bulk to thin film conditions. Angle variability in ASTM B117 can influence corrosion rate. Abstract: A sensor to determine water layer (WL) thickness, ranging from 0−5 mm, in salt-spray testing is presented. WL thickness is based on electrical resistivity and sensor design was guided by Finite Element Modeling with validation under known WL thicknesses. WLs were measured in continuous salt spray testing and angle of exposure played the largest role in thicknesses. At angles greater than 20˚ from vertical, semi-periodic run-off decreased WLs up to 80 %. Finally, exposure angle determines if thin-film conditions are achieved, likely influencing corrosion rate and morphology. Allowances for sample angle in testing standards pose a potentially large source of variability.